Ecology – Main Concern for the Christian space of the 21st Century? Catholic and Orthodox Perspectives - Morariu, Maxim (Journal for the study of religions and ideologies, 2020)
Although ecology is an important contemporary topic, influencing the economic, ethical, philosophical and religious area, among others, there are still aspects which are not highlighted enough by contemporary researchers as far as its role and the potential consequences of its misunderstanding are concerned. Knowing this, we will try to emphasise why ecology should be considered an important issue of the 21stcentury and which are the perspectives of the Orthodox and Catholic Churches regarding this topic. Both Churches share a common vision and their leaders are deeply committed to the vision of a future society where the environment is protected and respected. Therefore, we will try to emphasise the visions of several charismatic leaders such as the Ecumenical Patriarch Bartholomew of Constantinople or Pope Francis regarding this aspect and to show which are the main points of their conception. We will also try to present them in the context of their times and of their confession and to analyse the way in which they continue the directions assumed by their confessional area, being part of the current Christian message. At the same time, we will try to underline the common points of their perception and to see the pragmatic grounds on which they base it and the practical proposals they put forward. Topics such as integral ecology and aspects such as the anthropological basis of ecological crises will be analysed on the basis of documents, including the pastoral letters of Patriarch Bartholomew and the Encyclical letters of the current Pontiff, among which Laudato Si.